2000
DOI: 10.1002/1529-0131(200005)43:5<1175::aid-anr28>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of intraarticular hyaluronan and albumin in the attenuation of fluid drainage from joints

Abstract: Hyaluronan and albumin act together at normal concentrations to conserve synovial fluid in the presence of raised drainage pressures. Hyaluronan has the greater effect, acting osmotically by way of a concentration polarization boundary layer. Attenuation of this effect in arthritic effusions with low hyaluronan concentrations is one of several factors limiting fluid accumulation and, hence, the size of the effusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…It should be noted here that the dissociation constant for the specific complex HA-HN, equal to 10 − 9 mol L − 1 (Maingonnat et al, 1999), is of the same order of magnitude as those for the non-specific complexes HA-BSA and HA-lysozyme, which are about 10 − 9 and 10 − 8 mol L − 1 respectively (Van Damme et al, 1994). Lysozyme is present in cartilage (Van Damme et al, 1994) and albumin is a major protein of synovial fluid (Scott et al, 2000), two areas which are also rich in HA. Knowing that the interactions involved in the complex HA-BSA (Xu et al, 2000) and in the complex HA-lysozyme (Van Damme et al, 1994) are electrostatic, and that a charge patch able to accommodate an HA decamer exists at the surface of human serum albumin (as Grymonpré et al (2001) have shown with integrated computer modeling), we suggest that the binding of HA to albumin and lysozyme might in fact be specific.…”
Section: Discussionmentioning
confidence: 63%
“…It should be noted here that the dissociation constant for the specific complex HA-HN, equal to 10 − 9 mol L − 1 (Maingonnat et al, 1999), is of the same order of magnitude as those for the non-specific complexes HA-BSA and HA-lysozyme, which are about 10 − 9 and 10 − 8 mol L − 1 respectively (Van Damme et al, 1994). Lysozyme is present in cartilage (Van Damme et al, 1994) and albumin is a major protein of synovial fluid (Scott et al, 2000), two areas which are also rich in HA. Knowing that the interactions involved in the complex HA-BSA (Xu et al, 2000) and in the complex HA-lysozyme (Van Damme et al, 1994) are electrostatic, and that a charge patch able to accommodate an HA decamer exists at the surface of human serum albumin (as Grymonpré et al (2001) have shown with integrated computer modeling), we suggest that the binding of HA to albumin and lysozyme might in fact be specific.…”
Section: Discussionmentioning
confidence: 63%
“…Further support for this assumption comes from the fact that convective fluid flow out of the joint cavity may be attenuated by SF osmotic pressure at high lubricant concentrations, and also by a concentration polarization phenomenon for large molecules in SF such as HA (McDonald and Levick, 1992;Sabaratnam et al, 2004;Scott et al, 2000). The secretion rates with no chemical stimulation will be considered to be basal levels.…”
Section: Of Synovial Fluid Lubricant Compositionmentioning
confidence: 99%
“…1 and 4). (ii) Endothelium is the chief site of resistance to plasma protein permeation, and the reflection of plasma protein by the interstitial layer is negligible (Scott et al, 2000a). (iii) Studies using Monastral blue show the development of endothelial leaks (Poli et al, 2001).…”
Section: Does Cytochalasin Treatment Affect the Synovial Interstitialmentioning
confidence: 99%